Upaya Alternatif Bagi Pemerintah Indonesia Dalam Mengurangi Dampak Negatif Kegiatan Pertambangan Di Indonesia - Wiwik Harjanti (Jurnal Risalah Hukum, 2006)
Mineral resources represent natural resources which can not be updated or non-renewable, which means once they are taken out and used up, they cannot return to their initial forms. For this reason, these mineral resources shall be viewed as natural asset and exploiting them shall be conducted wisely. In addition, its management has to consider the future needs. Indonesian government thinks of all its natural resources as capital to add the national income. Unhappily, this matter is done by exploitation and in a massive scale. Operation of mining in Indonesia often generates various negative impacts for the environment, social life, economic, traditional community culture and also local community culture. Moreover, mining concession regions frequently overlaps with rich forest region, which becomes the source and place of living of the traditional community. Therefore, Indonesian government ought to do both preventive or repressive means to reduce these negative impacts, for example by improving mining regulation and giving more attention to environmental management and also to the community, in this case traditional community residing around the mining location. Key words: sumber daya alam (natural resources), tidak dapat diperbaharui (non-renewable), dampak negatif (negative impact), pertambangan (mining).